Поэтика комического и контекст (Рассказ А. Т. Аверченко «Праведник») [A Comic Narrative in Context: Arkady Averchenko’s Short Story “Pravednik”] - Nikolayev, Dmitri (Slavica Revalensia, 2017)
The present article addresses the problem of the context’s contribution to the readers’ perception of a certain text as humorous. It is a case study of the short story “Pravednik” (1904, 1908, 1910) by Arkady Averchenko. The study demostrates that in each publication during Averchenko’s lifetime this story was either becoming more serious and less humorous or less serious and more humorous—depending on the immediate context.